Scientific Literacy in Asia: Insights from the Top-Performing Economies in PISA 2022 - Wu, Yi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
The results reveal that socioeconomic status (ESCS) strongly affects scientific literacy across all five economies, with a particularly pronounced impact in Singapore and Japan. Teacher qualifications, especially the proportion of educators with doctoral degrees, significantly contribute to student performance in South Korea and Chinese Taipei. Additionally, school competition and creative learning environments play varying roles; while Singapore and Macao benefit from structured creativity programs, South Korea’s highly competitive environment leads to performance disparities. Psychological factors such as stress resistance and perseverance exhibit mixed effects. In South Korea, stress resistance positively correlates with achievement, whereas in Macao, it negatively impacts performance. Furthermore, student-teacher relationships significantly enhance literacy outcomes in Japan, emphasizing the role of positive academic interactions. These findings highlight the diverse yet interconnected educational strategies driving scientific literacy in Asia’s top-performing regions. The study underscores the importance of equitable resource distribution, teacher professional development, and balanced competitive environments in shaping student success. Policymakers can leverage these insights to refine educational frameworks globally, fostering scientific literacy while addressing disparities in STEM education.